In vitro isolation, regeneration and purification of yellow mutant in chrysanthemum (Chrysanthemum morifolium) cv. Lalit through ray floret regeneration - KUMAR, GUNJEET; SINDHU, S S; KUMAR, SURENDRA; VANLALRUATI, VANLALRUATI (The Indian Journal of Agricultural Sciences, 2017)
Mutations, induced or spontaneous, play an important role in inducing genetic variations in chrysanthemum (Chrysanthemum morifolium Ramat.). Isolation and purification of mutated tissue is impossible through conventional methods that results complete loss of the precious mutants due to lack of suitable techniques to isolate them through conventional methods. In the present investigation, an effort was made to develop efficient ray floret regeneration protocols to isolate, purify and establish a novel mutant which spontaneously appeared as chimera in the form of yellow flowers in chrysanthemum (Chrysanthemum morifolium) cv. Lalit (white). Maximum survival (82.0%) and callus formation (90.28%) in minimum duration (6.6 days) were recorded when the ray florets were pre-treated with mancozeb-45 (0.2%) + carbendazim (0.2%) + 8-HQC (200 mg/l) for 3 h followed by surface sterilized with HgCl2 (0.1%) for a duration of four minutes and cultured on Murashige and Skoog (MS) medium supplemented with 6-Benzylaminopurine (BAP) (4.0 mg/l) and NAA (1.0 mg/l). The maximum regeneration of micro-shoots (80%) from the ray floret induced callus was recorded on MS medium fortified with BAP (4.0 mg/l), NAA (0.5 mg/l) and gibberellic acid (GA3) (0.1 mg/l). MS medium supplemented with BAP (4.0 mg/l) + NAA (0.05 mg/l) + GA3 (0.1 mg/l) was found to be best for highest micro-shoot proliferation (92.0%). Highest rooting (86.0%) was induced after culturing the micro-shoots individually on half-strength MS medium fortified with 0.5 mg/l NAA and 50 g/l sucrose. Successful acclimatization of in vitro raised plantlets was done in glass jar with polypropylene cap filled with a mixture of sterilized coco-peat, soilrite and perlite (1:1:1) supplemented with half-strength MS inorganic salts. After 3-4 weeks of acclimatization, the plantlets were successfully transferred to ambient conditions and compared with the parent variety Lalit. The in vitro raised plants produced all bright yellow flowers as compared to the original variety Lalit with white flowers.